Electronic tongue: An analytical gustatory tool - Rewanthwar Swathi Latha; P K Lakshmi (Wolters Kluwer Medknow Publications, 2012)
Taste is an important organoleptic property governing acceptance of products for administration through mouth. But majority of drugs available are bitter in taste. For patient acceptability and compliance, bitter taste drugs are masked by adding several flavoring agents. Thus, taste assessment is one important quality control parameter for evaluating taste-masked formulations. The primary method for the taste measurement of drug substances and formulations is by human panelists. The use of sensory panelists is very difficult and problematic in industry and this is due to the potential toxicity of drugs and subjectivity of taste panelists, problems in recruiting taste panelists, motivation and panel maintenance are significantly difficult when working with unpleasant products. Furthermore, Food and Drug Administration (FDA)-unapproved molecules cannot be tested. Therefore, analytical taste-sensing multichannel sensory system called as electronic tongue (e-tongue or artificial tongue) which can assess taste have been replacing the sensory panelists. Thus, e-tongue includes benefits like reducing reliance on human panel. The present review focuses on the electrochemical concepts in instrumentation, performance qualification of E-tongue, and applications in various fields.